Pengembangan Game Edukasi Penyeberangan Jalan (Pelan) Menggunakan Kinect Sebagai Pengendali Permainan (Studi Kasus Di TK RAM NU 10 Banin-Banat Gresik) - Indi Rachmah Winona; Muhammad Aminul Akbar; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
People often crossing the road that isn't in the right place, they do any ways to get to their destination immediately, both riders and pedestrians haven't any awareness of safety in traffic. This can be triggering an accident and also can cause the death. Especially for parents who neglect to keep their children and let them play as they like without parents' control, so unconsciously the danger can threaten the children safety. In this research was done the development of educational game for crossing the roads in different and exciting ways through the application of game technology by using natural interaction called NUI i.e. Kinect technology, where it became an advantage for early childhood that playing the game with a natural movement without needed to touch or use a game controller. Fun testing results in this study was obtained from the questionnaires which was filled out by the testers and calculated through the calculation of Likert-scale index interpretation was obtained the result that the overall game presented was 76%, the game's display was 100%, the fun element in the game was 84%, and the difficulty level of the game was 72%.